(untitled) (Vallis Aurea, 2023)
Managers tend to sense, that many employees could do more. The question is: What can we do to influence them to contribute more than job description reguqires? Herzberg answer it, but his Two-Factor Theory has not received strong support in the literature. Accordingly, the basic objective of this scientific debate is to examine the relevance Herzberg motivation theory in terms of the new work economy. Scientific research methods applied in confirming the working hypothesis about the ghost of Herbzerg motivation theory based on scientific methods of analysis and synthesis, methods of descriptive statistics, method of mathematical modeling and method of mathematicalprogramming. The resulting findings suggest that any manager should not ignore its recommendations.